An Analysis of Cloud Computing's Resource Allocation Methods - A. Shenbaga Bharatha Priya, (AG Volumes, 2022)
In order for a cloud subscriber to run their applications on many platforms, anywhere, at any time, utilising just the resources given by the cloud service provider, the cloud service providers play a critical role. As a result, cloud customers must still deal with the challenge of quickly accessing the computing resources they need. For many users in several applications, this will have an effect on the service time and service level agreements. As a consequence, earlier research on cloud resource allocation need to be completed. This study examines the distribution and management of cloud computing resources. There is a lot of discussion here on alternative resource allocation systems and the difficulties they pose.